The Association of Religious Affiliation and Body Mass Index (BMI): An Analysis from the Health Survey for England - Lycett, Deborah (Journal of religion and health, 2015)
Obesity and obesity-related morbidity and mortality are an ongoing concern in developed countries. Religion is associated with reduced premature mortality and morbidity. However, the association between religion and obesity is unclear and unexplored in the general English population. This cross-sectional study uses Health Survey for England 2012 data to investigate the association of religious affiliation and BMI. A representative sample of 7,414 adults (16 years or older) was included. Waist-to-hip ratio was measured in a smaller sample and was explored as a secondary outcome. Interviews were administered, questionnaires self-completed, and height and weight measured. Sequential linear regression models were used to adjust for health behaviours. Religious affiliation was associated with a 0.91 kg/m2 higher BMI. Some of this was explained demographically, but it was not accounted for by smoking status, alcohol consumption or physical activity level. Evidence of this association was strongest among those affiliated to a Christian religion. A significantly higher WHR was also seen in Christian and Sikh men. English prospective studies measuring intrinsic religiosity and dietary energy are needed. Religious communities may need greater healthy weight promotion or benefit from tailored interventions built on their beliefs.